The Effectiveness of Role Play in Improving Speaking Skill of EFL Students - Alfina Dwiyanti; Yuri Lolita (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2023)
The purpose of this study is to see whether utilizing role play techniques may help Junior High School students improve their speaking abilities. A total of 68 students from the Surabaya’s Junior High School participated in this study. A quasi experimental research has been used in this study. The experimental group and control group, each of which had 34 students, were the two classes that were analysed. Role play techniques were used in the experiment group, and conventional techniques were used in the control group. Independent samples test was used to analyse the research data, which was then provided as quantitative data. The average score of students after the oral test was given using the conventional technique was only 71.25 in the control group and 76.97 in the experimental group. The average score of students after the oral test was given using the role play technique was 81.08 in the control group and 87.64 in the experimental group. As a result, students who are taught using Role play techniques receive higher scores than those who are not.